Inventory of Meat Randang Recipes In The City of Solok. - Eka Ulfi Aulia; Elida Elida (Universitas Negeri Padang, 2021)
Randang is food originating from Minangkabau, which is made from beef using spices and coconut milk. Inventory is an activity of recording or collecting data on the type of activity, the results to be achieved as well as about culture and so on. A recipe is an indication in which there is an explanation starting from what we are going to make and what are the ingredients and the amount to the processing that can make it easier for someone to do it. Until now, there has been no written recipe such as books, magazines and others explaining the ingredients, seasonings, processing equipment, and processing of beef randang in Solok City. The first objective of this research is to record the number of beef randang recipes in Solok City including Lubuk Sikarah and Tanjung Harapan Districts, and the second objective is to describe the ingredients and spices used to process meat randang. This study used data reduction methods, data presentation, cinclusion drawing / verification and conducting direct interviews with bundo kanduang, people who are experts in making meat randang The kelurahan has 39 different recipes for randang meat. The ingredients used are meat and coconut milk, the spices used consist of wet and dry spices and leaves. The equipment used to process meat randang is stale sanduak, stove and stale cauldron. Processing process There are 2 meat randang in Solok City, the first is that all the spices are cooked with coconut milk until the oil appears, then the meat is added. Both all the spices are sautéed and after stir-frying, add the coconut milk and then cook it until the oil rises and then the meat is added. The end result of the processing of randang is that the meat is black and oily.